ANALISIS SENTIMEN PERBANDINGAN LAYANAN JASA PENGIRIMAN KURIR PADA ULASAN PLAY STORE MENGGUNAKAN METODE DECISION TREE DAN RANDOM FOREST - Dellavianti Nishfi Ilmiah Huda; Cahyo Prianto; Rolly Maulana Awangga (LPPM Universitas Putera Batam, 2023)
Courier delivery is a crucial aspect of the e-commerce industry, and customer satisfaction with delivery services can significantly impact a company’s reputation, whether positive or negative. Therefore, sentiment analysis of customer reviews on the Play Store platform can provide valuable insights into the performance and acceptance of various courier delivery services available. This Study aims to conduct sentiment analysis on reviews of courier delivery services using two classification methods: Random Forest and Decision Tree. The first step in this research is data pre-processing, which includes text cleaning, tokenization, and the removal of irrelevant words. Subsequently, relevant features are extracted from the review texts using suitable feature extraction methods. Both Random Forest and Decision Tree methods are implemented to classify reviews from three companies: Pt X, Pt Y, and Pt Z, into two sentiment categories: positive and negative.The performance of both methods is evaluated using standard evaluation metrics. Furthermore, it is expected that this research will provide valuable information to the three e-commerce companies and courier service providers in improving the quality of their services based on customer feedback. Additionally, it can serve as a reference for consumers in choosing a courier delivery company that suits their needs.